2017
DOI: 10.1002/admi.201700481
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring Ni2P Sheets on NiCo2O4 Nanocone Arrays as Optimized Bifunctional Electrocatalyst for Water Splitting

Abstract: Bifunctional electrocatalyst is promising for the overall water splitting with high efficiency. Herein, inspired by the superior oxygen evolution reaction (OER) performance of transition metal oxide and remarkable hydrogen evolution reaction (HER) activity of transition metal phosphide, hierarchical NiCo2O4/Ni2P core–shell nanocone array on Ni foam is synthesized. The synergetic effect between the NiCo2O4 “core” and the Ni2P “shell” results in dramatically enhanced catalytic performance. It shows higher activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 54 publications
(70 reference statements)
0
21
0
Order By: Relevance
“…The observed two significant peaks at 856.78 and 875.18 eV for Ni 2 P, 856.83 and 875.23 eV for Ni 2 P/Ni 12 P 5 , and at 856.63 and 875.03 eV for Ni 12 P 5 correspond to the spin–orbital splitting of Ni 2p 3/2 and Ni 2p 1/2 , respectively. The respective binding energies substantiate the existence of surface-oxidized nickel species in the Ni 2+ oxidation state. , Also, it is observed that the peaks obtained at 852.21, 852.90, and 852.35 eV in Ni 2p spectra of Ni 2 P, Ni 2 P/Ni 12 P 5 , and Ni 12 P 5 , respectively, are quite close to the elemental-zero valence state of nickel, which conveys the small positive charge (Ni δ+ ) of Ni species in the prepared samples. The P 2p spectrum of Ni 2 P shows a prominent peak around 133.62 eV and a marginal hump at 129.20 eV, which can be attributed to the oxidized P species and metallic P, respectively, whereas the P 2p spectra show two prominent peaks around 129.77, 134.34 eV on behalf of Ni 2 P/Ni 12 P 5 and 129.82, 134.32 eV intended for Ni 12 P 5 , which could be assigned to P δ− in the form of metal phosphide and oxidized P species observed at the surface due to the partial passivation of phosphide particles. , The P 2p binding energy at ∼129.20 eV is less than that of elemental P (130.20 eV), which indicates that the P species in Ni 2 P has a minimal negative charge (P δ− , 0 < δ < 1). , These results suggest that there is an electron transfer from Ni to P in all three nickel phosphide phases. Because of the XPS studies taken for the aged Ni–P samples after a year, the conspicuous presence of oxidized Ni and P peaks have been attributed to the surface oxidation of the sample.…”
Section: Resultsmentioning
confidence: 63%
“…The observed two significant peaks at 856.78 and 875.18 eV for Ni 2 P, 856.83 and 875.23 eV for Ni 2 P/Ni 12 P 5 , and at 856.63 and 875.03 eV for Ni 12 P 5 correspond to the spin–orbital splitting of Ni 2p 3/2 and Ni 2p 1/2 , respectively. The respective binding energies substantiate the existence of surface-oxidized nickel species in the Ni 2+ oxidation state. , Also, it is observed that the peaks obtained at 852.21, 852.90, and 852.35 eV in Ni 2p spectra of Ni 2 P, Ni 2 P/Ni 12 P 5 , and Ni 12 P 5 , respectively, are quite close to the elemental-zero valence state of nickel, which conveys the small positive charge (Ni δ+ ) of Ni species in the prepared samples. The P 2p spectrum of Ni 2 P shows a prominent peak around 133.62 eV and a marginal hump at 129.20 eV, which can be attributed to the oxidized P species and metallic P, respectively, whereas the P 2p spectra show two prominent peaks around 129.77, 134.34 eV on behalf of Ni 2 P/Ni 12 P 5 and 129.82, 134.32 eV intended for Ni 12 P 5 , which could be assigned to P δ− in the form of metal phosphide and oxidized P species observed at the surface due to the partial passivation of phosphide particles. , The P 2p binding energy at ∼129.20 eV is less than that of elemental P (130.20 eV), which indicates that the P species in Ni 2 P has a minimal negative charge (P δ− , 0 < δ < 1). , These results suggest that there is an electron transfer from Ni to P in all three nickel phosphide phases. Because of the XPS studies taken for the aged Ni–P samples after a year, the conspicuous presence of oxidized Ni and P peaks have been attributed to the surface oxidation of the sample.…”
Section: Resultsmentioning
confidence: 63%
“…[1][2][3][4][5][6][7] Hydrogen is an ideal alternative energy sources with the advantages of high energy, non-toxic, non-pollution and recycling. [8][9][10][11][12][13] The development of hydrogen economy is a permanent strategic choice for mankind to get rid of dependence on fossil energy [14] and the electrocatalytic water splitting is widely regarded as a promising strategy to generate hydrogen via the energy conversion of electricity . [15][16][17] Nevertheless, as a half reaction during water splitting, [18,19] oxygen evolution reaction (OER) is a kinetically sluggish four-electron multistep transfer process and an uphill process in thermodynamics , [20][21][22][23] thus seriously affecting the other half reaction, i. e. hydrogen evolution reaction (HER), to produce hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…With the growing demand for green energy resources, a great variety of efforts have been devoted to the searches and developments for renewable and alternative energy . Hydrogen is an ideal alternative energy sources with the advantages of high energy, non‐toxic, non‐pollution and recycling . The development of hydrogen economy is a permanent strategic choice for mankind to get rid of dependence on fossil energy and the electrocatalytic water splitting is widely regarded as a promising strategy to generate hydrogen via the energy conversion of electricity .…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly growing energy consumption and severe environmental pollution have aroused wide public concern over recent years, reflecting a burning issue to explore alternative and sustainable energy conversion and storage systems to deal with the current crisis. , As an effective means of generating molecular oxygen through the process of electrochemical water oxidation, the oxygen evolution reaction (OER) plays a crucial role in many fields associated with energy conversion and storage, such as water splitting and metal–air batteries. However, its complicated four-electron transfer process leads to the sluggish kinetics and requirement of high overpotential, ultimately restricting the overall efficiency of energy conversion. As a consequence, it is of utmost urgency to develop OER electrocatalysts with low overpotential, high efficiency, and long-term stability to accelerate the reacting process of the OER. IrO 2 and RuO 2 have been considered as the benchmark of OER electrocatalysts, whereas the constraints of resource scarcity and high cost severely prohibit their widespread applications, further stimulating the search for earth-abundant and low-cost transition-metal-based OER catalysts to replace these noble-metal oxides. …”
Section: Introductionmentioning
confidence: 99%